Lo stile tardo in Bassani, Fortini, Pasolini - Bianco, Yole Deborah; Gatto, Marco; Perrelli, Raffaele; Luglio, Davide (Università della Calabria, 2025)
Late Style in Bassani, Fortini and Pasolini This thesis investigates the aesthetic and hermeneutic category of late style (Spätstil), theorized by Theodor W. Adorno in his fragmentary writings on Beethoven’s late works, and subsequently expanded upon by Edward Said. In its first part, the research offers a reading of Adorno’s reflections on Beethoven’s late oeuvre, unpacking a series of its defining features. The study thus redefines late style not merely as the result of artistic old age, but as an expression of historical crisis, fragmentation, and a “sense of the end.” Furthermore, the thesis seeks to frame late style as a historical-epochal category, highlighting how it reflects the tensions of specific cultural and historical contexts. The second part applies this category to three major Italian authors of the late twentieth century: Giorgio Bassani, Franco Fortini, and Pier Paolo Pasolini. L’airone and Bassani’s final poems are read as expressions of nihilistic dissolution; Questo muro, Paesaggio con serpente, and Composita solvantur by Fortini embody an allegorical metamorphosis and a landscape of petrified forms; Pasolini’s La nuova gioventù, together with the unfinished Petrolio and his final film Salò, instead represent a “late style without a late work,” volcanic and disruptive. By bringing these three case studies into dialogue, the thesis demonstrates how late style, beyond biographical aging, reflects a confrontation with historical crisis and with the limits of art. The comparative framework thus highlights divergent responses to the experience of the end: nihilistic closure (Bassani), allegorical dissolution (Fortini), and explosive fragmentation (Pasolini).
Dottorato di ricerca in Studi umanistici, Ciclo XXXVII, In cotutela con Sorbonne Universitè-LLHS, ED20, École doctorale civilitations, cultures, littératures et sociétés, a.a. 2024-2025
Keywords: Bassani Giorgio; Fortini Franco; Pasolini Pier Paolo